2005
DOI: 10.1080/13607860500131047
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about mental illness and willingness to seek help: A cross-sectional study

Abstract: Evidence indicates that older adults underutilize mental health services, but little is known empirically about the perceptions older adults have about mental illness and their attitudes about seeking professional help for psychological problems. The present study examined beliefs about mental illness and willingness to seek professional help among younger (n=96; M age=20.6 years; range=17-26 years) and older (n=79; M age=75.1 years; range=60-95 years) persons. Participants completed the Beliefs Toward Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
94
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 20 publications
18
94
4
3
Order By: Relevance
“…Furthermore, the participants seldom reported fear of being stigmatized as a reason for not seeking help. These results are in line with recent findings, which indicate that older adults are progressively open to mental health treatment, displaying positive attitudes towards help seeking (Mackenzie, Scott, Mather, & Sareen, 2008;Mohlman, 2012;Segal, Coolidge, Mincic, & O'Riley, 2005). Nevertheless, the likelihood of seeking help for mental health problems still decreased with age.…”
Section: Page 7 Of 16supporting
confidence: 92%
“…Furthermore, the participants seldom reported fear of being stigmatized as a reason for not seeking help. These results are in line with recent findings, which indicate that older adults are progressively open to mental health treatment, displaying positive attitudes towards help seeking (Mackenzie, Scott, Mather, & Sareen, 2008;Mohlman, 2012;Segal, Coolidge, Mincic, & O'Riley, 2005). Nevertheless, the likelihood of seeking help for mental health problems still decreased with age.…”
Section: Page 7 Of 16supporting
confidence: 92%
“…Mental health stigma can lead individuals to feel ashamed, think of themselves as weak, and lose self-respect-all of which can increase distress and social problems and decrease willingness to seek treatment [24]. Stigma related to mental health diagnoses and treatment is particularly salient within the older adult population and has been associated with decreased satisfaction with mental health treatment [25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the presence of such attitudes in Nigeria (Gureje et al, 2005); they are informed and reinforced by traditional, cultural and religious beliefs about the causes of mental illness (Gureje et al, 2006) and have been shown to inhibit help-seeking behaviour (Segal et al, 2005). Furthermore, beliefs about and attitudes to mental illness among healthcare professionals can influence treatment outcomes (Schulze, 2007).…”
mentioning
confidence: 99%